2018
DOI: 10.1016/j.meegid.2018.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting priority areas for bovine viral diarrhea control in Italy: A phylogeographic approach

Abstract: The prevalence and genetic diversity of bovine viral diarrhea virus (BVDV) in a geographic area are largely influenced by live animal trade and management practices. Despite control and eradication programs currently underway in several European countries, the risk of BVDV spread within and among countries is still present. BVDV-1 is the predominant type circulating in European cattle population. In this study, a phylogeographic analysis was applied to the BVDV-1 highest prevalent subtypes in Italy to reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…As shown above, the genetic spectrum of bovine pestiviruses was very narrow, with two subgenotypes associated with each of the two cattle breeds. Although the size of the Italian cattle population is only 5 to 5.5 million, the genetic diversity of pestiviruses in Italy is very high, with BVDV-2, HoBi-like pestivirus, and some 18 different subgenotypes of BVDV-1 [45, 60, 61]. This high level of diversity can be explained by a long tradition of importing large numbers of cattle of unknown BVD status from different countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown above, the genetic spectrum of bovine pestiviruses was very narrow, with two subgenotypes associated with each of the two cattle breeds. Although the size of the Italian cattle population is only 5 to 5.5 million, the genetic diversity of pestiviruses in Italy is very high, with BVDV-2, HoBi-like pestivirus, and some 18 different subgenotypes of BVDV-1 [45, 60, 61]. This high level of diversity can be explained by a long tradition of importing large numbers of cattle of unknown BVD status from different countries.…”
Section: Resultsmentioning
confidence: 99%
“…For bovine, porcine and ovine pestiviruses, the time of divergence from a common ancestor was calculated to the year 1483, with a wide margin for the highest posterior density HPD 95 of 600 to 1892. The emergence of BVDV-1 and BVDV-2 from a putative ancestor was calculated to a time between 1629 to 1736 [70], and that of the emergence of BVDV-1b and -1e to a time between 1889 to 1950 and 1957 and 1988, respectively [61].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BVDV-1e represented by strain 217-SM/18 has been identified only in one Polish herd. It had 98% nucleotide similarity to the Italian BVDV-1e strain from Northern Italy [28]. This subtype was found also in Switzerland [29] and France [30].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, a study performed in Germany, it was found both the BVDV-1 and 2 as well [30]. When the species were typed, BVDV-1a was found in all of them, even when the most frequent genotype is 1b [2, 4, 31, 32]. Just a few regions have this type as a predominant [33].…”
Section: Discussionmentioning
confidence: 99%